Hypertriglyceridemia associated with the c.553G>T APOA5 SNP results from aberrant hetero-disulfide bond formation - Sharma, Vineeta (2014)
OBJECTIVE: Apolipoprotein (apo) A-V is a low abundance plasma protein that modulates triacylglycerol (TG) homeostasis. Gene transfer studies were undertaken in apoa5 (−/−) mice to define the mechanism underlying the correlation between the single nucleotide polymorphism (SNP) c.553G>T in APOA5 and hypertriglyceridemia (HTG). APPROACH AND RESULTS: Adeno-associated virus (AAV) 2/8 mediated gene transfer of wild type (WT) apoA-V induced a dramatic lowering of plasma TG in apoa5 (−/−) mice while AAV2/8-Gly162Cys apoA-V (corresponding to the c.553G>T SNP: rs2075291) had a modest effect. Characterization studies revealed that plasma levels of WT- and G162C apoA-V in transduced mice were similar and within the physiological range. Fractionation of plasma from mice transduced with AAV2/8-G162C apoA-V indicated that, unlike WT apoA-V, >50% of G162C apoA-V was recovered in the lipoprotein-free fraction. Non-reducing SDS-PAGE immunoblot analysis provided evidence that G162C apoA-V present in the lipoprotein-free fraction, but not that portion associated with lipoproteins, displayed altered electrophoretic mobility consistent with disulfide-linked hetero-dimer formation. Immunoprecipitation followed by liquid chromatography/mass spectrometry of human plasma from subjects homozygous for WT APOA5 and c.553G>T APOA5 revealed that G162C apoA-V forms adducts with extraneous plasma proteins including fibronectin, kininogen-1 and others. CONCLUSION: Substitution of Cys for Gly at position 162 of mature apoA-V introduces a free cysteine that forms disulfide bonds with plasma proteins such that its lipoprotein binding and TG modulation functions are compromised.